In vitro Assessment of the Biofield Treated Test Item on Cardiac Function Using Rat Cardiomyocytes Cell Line (H9c2) via Multiparametric Analysis - Mahendra Kumar Trivedi; Snehasis Jana (Journal of Hypertension and Cardiology, 2019)
Introduction Heart disorders are the major concern of population health worldwide. According to WHO estimates 2018, 17.9 million peoples were died due to cardiovascular disorders. Aim The aim of this study was to investigate the cardioprotective activity of Biofield Energy Treated test item, Dulbecco's Modified Eagle Medium (DMEM) using rat cardiomyocytes (H9c2). Methods The test item (DMEM) was divided into three parts, first part received one-time Biofield Energy Treatment by a renowned Biofield Energy Healer, Mahendra Kumar Trivedi and was labeled as the one-time Biofield Energy Treated (BT-I) DMEM, while second part received the two-times Biofield Energy Treatment and is denoted as BT-II DMEM. The third part did not receive any treatment and defined as the untreated DMEM group. Results Cell viability of the test samples by 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide (MTT) assay showed 89.03% and 98.49% in the BT-I and BT-II groups, respectively suggested a nontoxic and safe in nature of the tested test item. The BT-I group showed 16.01% restoration of cell viability. The level of lactate dehydrogenase (LDH) was significantly inhibited by 50.37% and 49.35% in the BT-I and BT-II groups, respectively compared to the untreated DMEM group. Moreover, percent protection of creatine kinase-myocardial band (CK-MB) by 49.48% and 59.79% in the BT-I and BT-II groups, respectively, compared to the untreated DMEM group. Reactive oxygen species (ROS) level in terms of mean fluorescence unit (FU) was reduced by 6.64% in the BT-I group than untreated DMEM. Besides, BT-I and BT-II groups significantly increased the level of % apoptotic cells by 63.16% and 97.37% (p≤0.05), respectively than untreated DMEM. Conclusion Allover, results envisaged that Biofield Treatment significantly improved different cardiac parameters. Thus, Biofield Energy Treatment (The Trivedi Effect®) could be utilized as a cardio-protectant against several cardiac disorders such as coronary artery disease, heart attack, arrhythmias, heart failure, congenital heart disease, cardiomyopathy, etc.
Keywords: Biofield Energy Treatment